Ibu Tangguh, Bayi Terlindungi : Upaya Penguatan Kapasitas dalam Pencegahan Infeksi - Harwin Holilah Desyanti; Nurul Lailatul Arofah; Mita Ayu (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
This community service program is designed to enhance mothers' capacity to prevent infections in infants and toddlers in Sumber Kokap Village, Bondowoso Regency, which faces limited access to health information and services. Utilizing a community-based participatory approach, the program involves mothers, health volunteers, and community leaders in educational activities that include needs assessments, group discussions, and training on hygiene practices and early infection detection. Findings indicate a significant improvement in mothers' understanding of the importance of infection prevention, as well as strengthened community support for implementing preventive health practices. This intervention is expected to contribute to a reduction in maternal and neonatal infection incidence and serve as a model for health empowerment in rural communities.